2010 Global Hunger Index: The challenge of hunger: Focus on the crisis of child undernutrition - von Grebmer, Klaus; Ruel, Marie T.; Menon, Purnima; Nestorova, Bella; Olofinbiyi, Tolulope; Fritschel, Heidi; Yohannes, Yisehac; von Oppeln, Constanze; Towey, Olive; Golden, Kate; Thompson, Jennifer (International Food Policy Research Institute, 2010)
As the world approaches the 2015 deadline for achieving the Millennium Development Goals (MDGs)—which include a goal of reducing the proportion of hungry people by half—the 2010 Global Hunger Index (GHI) offers a useful multidimensional overview of global hunger. The 2010 GHI is the fifth in an annual series that records the state of global, regional, and national hunger. The 2010 GHI shows some improvement over the 1990 GHI, falling by almost one-quarter, but overall the index for hunger in the world remains at a level characterized as serious.